Political communication: uncovering knowledge, attitudes and young voters readiness for PRU-15 in Batang Padang District, Perak - Siti Nor Amalina Ahmad Tajuddin (Tanjung Malim, 2023)
Political communication: uncovering knowledge, attitudes and young voters readiness for PRU-15 in Batang Padang District, Perak by Siti Nor Amalina Ahmad Tajuddin